Catherine Claeyé. (Antwerpen Burcht, 2002)
Photo book after a three months during project with hanging cabbages on the bank of the river Schelde, Antwerp, Belgium
Engels
Catherine Claeyé. Schelde Burcht, Antwerpen, 2000-08-12. 2000-10-15
boek
Keywords: Claeyé, Catherine